Complementary Patents and Market Structure - Klaus M. Schmidt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
Many high technology goods are based on standards that require access to several patents that are owned by different IP holders. We investigate the royalties chosen by IP holders under different market structures. Vertical integration of an IP holder and a downstream producer solves the double mark-up problem between these firms. Nevertheless, it may raise royalty rates and reduce output as compared to non-integration. Horizontal integration of IP holders (or a patent pool) solves the complements problem but not the double mark-up problem. Vertical integration discourages entry and reduces innovation incentives, while horizontal integration always encourages entry and innovation.
urn:nbn:de:bvb:19-epub-13303-2
Keywords: L15; O31; L24; O32; K11; 330